2016
DOI: 10.1371/journal.pone.0156618
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Loop C Hydrophilic Residue ‘T244’ in the Binding Site of ρ1 GABAC Receptors via Site Mutation and Partial Agonism

Abstract: The loop C hydrophilic residue, threonine 244 lines the orthosteric binding site of ρ1 GABAC receptors was studied by point mutation into serine, alanine and cysteine, and tested with GABA, some representative partial agonists and antagonists. Thr244 has a hydroxyl group essential for GABA activity that is constrained by the threonine methyl group, orienting it toward the binding site. Significant decreases in activation effects of the studied ligands at ρ1 T244S mutant receptors, suggests a critical role for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It is made up of 20 residues that are directly or indirectly involved in GABA binding 30 ; two of these residues, located in one of each subunit (Y198 in the + subunit and S168 in the − subunit), are involved in the recognition of the amine group of GABA. The acidic group of GABA is bound to R104 31 and T244 32 (in the − and + subunit, respectively) (Fig. 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is made up of 20 residues that are directly or indirectly involved in GABA binding 30 ; two of these residues, located in one of each subunit (Y198 in the + subunit and S168 in the − subunit), are involved in the recognition of the amine group of GABA. The acidic group of GABA is bound to R104 31 and T244 32 (in the − and + subunit, respectively) (Fig. 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports showed that residues T224 and R104 are critical for interacting with the acidic moiety of GABA and channel gating. Mutations in R104 induce a reconfiguration of the GABA binding site unable to gate the channel 32 , whereas mutation T224A reduces the efficacy of GABA 33 . In our docking model, DOPAC is less than 5 Å from T224 and R104, but the larger distance to Y198 and S168 (more than 7 Å) would make the hydrogen bonds unstable.…”
Section: Discussionmentioning
confidence: 99%
“…A range of agonists studied at the T244S mutant receptor demonstrated many‐fold decreases in potency, while antagonist activity remained unaffected by the mutation (Yamamoto et al, ). Thr 244 is proposed to be essential for the formation of an H‐bond with agonists initiating conformational changes through movement of Loop C to open the channel (Naffaa et al, ).…”
Section: Gaba‐ρ1 Agonist Binding Sitementioning
confidence: 99%
“…We subsequently implemented two-electrode voltage-clamp electrophysiology (TEVC) to record the pharmacological effect of the ligands in this study at GABA-2 receptors expressed on the membrane of Xenopus oocytes. The GABA analogues used in this work were chosen because they have previously shown interesting pharmacological profiles at GABA-1 WT (wild type) and mutant receptors [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Models of GABA-bound GABA-2 were built based on the GABA-1 model in an open conformation using Prime 3.2 software [24]. These generated models were reviewed and verified as described in our previous published work [19].…”
Section: Introductionmentioning
confidence: 99%